AESTHETIC OF WORKING STRUCTURE IN TARI PIRING HURIAH ADAM - Efrida Efrida (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2022)
Tari Piring Huriah Adam is a dance work that departs from the habits of the Minangkabau people in the agricultural world. Tari Piring is one of the arts of the Minangkabau community that uses a plate as property and a ring on the middle finger that is tapped to produce a sound according to the rhythm of the music. This dance has thirteen movement structures, all of which describe the life of the Minangkabau people. The creativity of the Minangkabau choreographer in strengthening the Minang ethnic identity is outlined in the creations of dance works that depart from the traditional Bamain Piriang dance. The concept to unravel this dance is the concept of structuralism, where a work of art is a fabric of elements that build it. Structuralism is a way of thinking about the world associated with perceiving and describing structures. A structure is a system consisting of an element, none of which can change without producing a difference in another aspect. The result of the analysis of the work is the creation of a work of art through a very neat relationship between structures.Keywords: dance; structure; agriculture; culture.ABSTRAKTari piring karya Huriah Adam merupakan karya tari yang berangkat dari kebiasaan orang Minangkabau dalam dunia pertanian. Tari piring merupakan salah satu kesenian masyarakat Minangkabau yang menggunakan piring sebagai properti dan menggunakan cincin di jari tengah yang diketukan sehingga menghasilkan bunyi sesuai irama musiknya. Tari ini memiliki struktur gerak yang berjumlah tiga belas yang semuanya menggambarkan tentang kehidupan orang Minangkabau. Kreativitas koreografer Minangkabau dalam menguatkan identitas etnis Minang yang dituangkan dalam karya-karya tari kreasi yang berangkat dari tari tradisional Bamain Piriang. Konsep untuk mengurai tari piring ini adalah konsep strukturalisme dimana sebuah karya seni merupakan jalinan unsur-unsur yang membangunnya. Strukturalisme adalah cara berpikir tentang dunia yang dikaitkan dengan persepsi dan deskripsi struktur. Struktur yang merupakan sebuah sistem, yang terdiri dari sebuah anasir, yang di antaranya tidak satu pun dapat mengalami perubahan tanpa menghasilkan perubahan dalam sebuah anasir lain. Hasil analisis karya adalah terbangunnya sebuah karya seni lewat hubungan antar struktur yang sangat rapi